Bleeding Risks in Patients on Percutaneous Ventricular Assist Devices Receiving Two Different Dextrose Concentrations of Heparinized Purge Solution: A Case Series. (August 2019) - Dietrich, Jenna N.; Kazmi, Hasan
Background: The Impella manufacturer has changed its recommendation for the diluent of the heparinized purge solution from 20% dextrose (D20) to 5% dextrose (D5). This reduced viscosity may result in increased purge solution infusion rates and unfractionated heparin (UFH) exposure. Increased UFH exposure could potentially cause increased bleeding events and may necessitate reduction in UFH concentration in the purge solution. Our objective was to evaluate anticoagulation for patients on Impella pumps receiving heparinized purge solution with D20 or D5 diluents. Methods: This retrospective cohort analysis evaluated patients requiring Impella support outside of the cardiac catheterization lab. The primary outcome evaluated the number of patients with at least one supratherapeutic activated partial thromboplastin time (aPTT) while receiving heparinized purge solution alone without systemic UFH. Secondary outcomes included heparin concentration changes made to the purge solution, bleeding, and thrombotic events. Results: Twelve patients received Impella support for an average of 37 hours (range, 10.8-89.6). Four patients received D20 and 8 patients received D5 purge solution. Five patients had at least one supratherapeutic aPTT while receiving heparinized purge solution alone without additional systemic UFH. All 5 patients were in the D5 group. Of these 5 patients, 3 required purge heparin concentration decreases and 3 had bleeding events. No patients had pump thrombosis. Conclusion: D5 purge solution with heparin 50 units/mL may increase the risk of supratherapeutic aPTTs, leading to increased bleeding. Decreasing heparin to 25 units/mL as a standard in purge solution may decrease these risks; however, protection against thrombosis remains unknown.